New and More Solitary Wave Solutions for the Klein-Gordon-Schrödinger Model Arising in Nucleon-Meson Interaction - Raza, Nauman; Arshed, Saima; Butt, Asma Rashid; Baleanu, Dumitru (Frontiers in Physics, 2021)
The aim of the current study is to extract exact, explicit and new single soliton solutions related to non-linear Klein-Gordon-Schrodinger model that is used to study a system of conserved scalar nucleons interacting with neutral scalar mesons coupled through the Yukawa interaction. Three state of the art integration schemes namely, tanh-coth expansion method, the e¡©(»)-expansion method and the Kudryashov's method are being employed to extract bright soliton, dark soliton, dipole soliton, combo soliton, kink soliton and singular soliton. All the constructed solutions satisfy their existence criteria. It is shown that these methods are concise, straight, promising and reliable mathematical tools to untangle the physical features of mathematical physics equations.